STUDI TENTANG MEDIA SOSIAL TERHADAP PENGEMBANGAN UKM MELALUI KEUNGGULAN BERSAING DAN IMPLEMENTASI MODEL A.I.D.A. pada UMKM pangan di Kota Semarang - Nugroho, Wildan Aryo; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2019)
The purpose of this study is to analyze analyze the effect of the marketing environment, innovation, and social media on the development of MSMEs with marketing strategies and competitive advantage as intervening variables and the effect of applying the AIDA model . The population in this study were Micro, Small and Medium Enterprises owners, where respondents were owners of Micro, Small and Medium Enterprises in the city of Semarang. The number of samples used was 150 respondents. The method of data collection is done through a questionnaire method. This study uses Structural Equation Modeling (SEM) analysis techniques using the AMOS 24 analysis tool.The results of this study indicate that the marketing environment has a positive and significant effect on marketing strategy, innovation has a positive and significant effect on marketing strategy and competitive advantage, social media has a positive and significant effect on competitive advantage, marketing strategy has a positive and significant effect on the development of MSMEs, and competitive advantage bar positive and significant impact on the development of MSMEs.